How Do Social Needs Cluster Among Low-Income Individuals? - Kreuter, Matthew W. (Popul Health Manag, 2021)
Social needs screening in health care settings reveals that many low-income individuals have multiple unmet social needs at the same time. Having multiple simultaneous social needs greatly increases the odds of experiencing adverse health outcomes. To better understand how and which social needs cluster in these cases, the authors examined data from 14,749 low-income adults who completed a social needs assessment in one of 4 separate studies conducted between 2008 and 2019 in the United States. Participants were Medicaid beneficiaries, helpline callers, and daily smokers. Findings were strikingly consistent across the 4 studies. Participants with ≥2 social needs (n = 5621; 38% of total) experienced more stress, depressive symptoms, sleep problems, and chronic diseases and were more likely to rate their health as fair or poor. Social needs reflecting financial strain were highly correlated, such as needing help paying utility bills and needing money for necessities such as food, shelter, and clothing (r = .49 to .71 across studies). Participants experienced 351 distinct combinations of ≥2 social needs. The 10 most common combinations accounted for more than half of all participants with ≥2 needs. Clusters of social needs varied by subgroups. Women with children were more likely than others to need more space in their home and help paying utility bills; low-income men were more likely to be physically threatened and need a place to stay; older, sicker adults were more likely to need money for necessities and unexpected expenses, as well as transportation. Findings are discussed in the context of creating smarter, more efficient social needs interventions.